Beyond Abdominal Pain: Decoding the Mysteries of Nutcracker Syndrome - Usamah Al-Anbagi (22330936) (2024)
Nutcracker syndrome (NCS), a rare but impactful vascular condition, emerges from the compression of the left renal vein by adjacent major arteries, leading to a diverse array of symptoms such as hematuria, flank pain, and renal challenges. Highlighting the case of a 30‐year‐old male with an atypical presentation of NCS, this report explores the diagnostic complexities arising from its varied presentations and therapeutic options. It emphasizes the critical role of computed tomography (CT) in unveiling the underlying vascular constriction. Through this lens, the case underscores the necessity of considering NCS in the differential diagnosis of abdominal pain, advocating for a prompt and accurate diagnosis to guide effective management strategies, ranging from conservative approaches to surgical intervention. This stresses the importance of heightened awareness and ongoing research for optimizing patient outcomes in the face of this elusive condition. Other Information Published in: Case Reports in Vascular Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/2024/8702202